Determinant Factors of Gojek Drivers' Interest in Using Social Security Administrator Employment in Medan City - Nurdiana Nurdiana; Andri Soemitra; Aqwa Naser Daulay (Borong Newinera Publisher, 2024)
The existence of insurance is intended for every individual because every individual has the right to receive guarantees from risks that occur in the future, insurance programs are mandatory for every society. However, it is very unfortunate that there are still many informal workers such as Gojek drivers who do not have life insurance coverage. This research aims to determine the determinant factors of drivers' interest in using Social Security Administrator (BPJS) Employment. The variables used are income, price, information, and service variables which can influence interest in using BPJS Employment. The sample used was 100 respondents. For data processing, researchers are assisted by Smart-PLS. From the test results, the researcher saw that there was a variable influence of income, price and information on interest in using BPJS Employment and the service variable had no positive and significant influence on interest in using BPJS Employment.